A new robust digital watermarking using local polar harmonic transform. (August 2015) - Wang, Xiang-yang; Liu, Yu-nan; Li, Shuo; Yang, Hong-ying; Niu, Pan-pan; Zhang, Yan
Graphical abstract: The PHT modulus distribution for image Barbara under various attacks: (a) Gaussian filtering, (b) JPEG compression 50, (c) rotation, (d) scaling. Highlights: The stable and uniform image feature points are extracted by the improved SURF detector. The affine invariant local feature regions are constructed adaptively. A new and effective 2D transform is introduced to embed watermark in the digital image. Abstract: Geometric distortions are more difficult to tackle than other types of attacks. It is a challenging work to design a robust image watermarking scheme against geometric distortions. In this paper, we propose a robust digital image watermarking scheme based on local polar harmonic transform. The proposed scheme has the following advantages: (1) the stable and uniform image feature points are extracted by the improved speeded-up robust feature (SURF) detector, in which the probability density gradient is utilized, (2) the affine invariant local feature regions are constructed adaptively according to the variation of local probability density, and (3) a new and effective 2D transform, named polar harmonic transform (PHT), is introduced to embed watermark in the digital image. Experiments are carried out on a digital image set of 100 images collected from Internet, and the preliminary results show that the proposed image watermarking is not only invisible and robust against common image processing operations such as filtering, noise adding, and JPEG compression, but also robust against the geometric distortions.